Myelin oligodendrocyte glycoprotein antibodies are associated with a non-MS course in children. Issue 2 (April 2015) - Hacohen, Yael; Absoud, Michael; Deiva, Kumaran; Hemingway, Cheryl; Nytrova, Petra; Woodhall, Mark; Palace, Jacqueline; Wassmer, Evangeline; Tardieu, Marc; Vincent, Angela; Lim, Ming; Waters, Patrick
Abstract : Objective: To determine whether myelin oligodendrocyte glycoprotein antibodies (MOG-Abs) were predictive of a demyelination phenotype in children presenting with acquired demyelinating syndrome (ADS). Method: Sixty-five children with a first episode of ADS (12 acute disseminated encephalomyelitis, 24 optic neuritis, 18 transverse myelitis, 11 other clinically isolated syndrome) were identified from 2 national demyelination programs in the United Kingdom and France. Acute serum samples were tested for MOG-Abs by cell-based assay. Antibodies were used to predict diagnosis of multiple sclerosis (MS) at 1 year. Results: Twenty-three of 65 (35%) children had MOG-Abs. Antibody-positive and antibody-negative patients were not clinically different at presentation, but identification of MOG-Abs predicted a non-MS course at 1-year follow-up: only 2/23 (9%) MOG-Ab–positive patients were diagnosed with MS compared to 16/42 (38%) MOG-Ab–negative patients ( p = 0.019, Fisher exact test). Antibody positivity at outset was a useful predictor for a non-MS disease course, with a positive predictive value of 91% (95% confidence interval [CI] 72–99), negative predictive value of 38% (95% CI 24–54), positive likelihood ratio of 4.02 (CI 1.0–15.4), and odds ratio of 6.5 (CI 1.3–31.3). Conclusions: MOG-Abs are found at presentation in 35% of patients with childhood ADS, across a range of demyelinating disorders. Antibody positivity can be useful in predicting a non-MS disease course at onset.